Spatialities of population change, mega-urbanization and neoliberal urbanism the case of Metro Cebu - Ortega, Arnisson Andre C. (2012)
In 2011, the newly established Metro Cebu Development Coordinating Board (MCDCB) along with its allied private sector groups launched the ambitious Mega-Cebu Project, a 30-year plan for building a globally-competitive mega region beyond the current city structure. Since the 'Ceboom' phenomenon in the 1990s, investment-oriented development has transformed Cebu City's urban space and expanded its development tendrils into surrounding areas. This paper attempts to explicate the spatially restless process of Cebu's mega-urbanization by using a spatio-demographic dialectic that argues for the mutual constitutiveness between population growth/decline and social, political and economic process. First, the study historicizes Cebu's urbanization. Second, it compares it growth with other major Philippine metropolitan areas. Lastly, actual spatial clusters of population growth and decline in Metro Cebu are identified and mapped over the years (1990-1995; 1995-2000; 2000-2007 and 2007-2010), from which accounts of development, mobilities, dispossessions and social, political and economic transaction are interwoven, What are unraveled in these demographic narratives are the recursive relations of capitalism and urbanization, which operate in local terrains and facilitate population growth and/or decline, and the political-economic logic of Cebu's urban trajectories that are instructive of the Mega Cebu Project's urban visions.
Keywords: Cebu City; Urbanization; Neoliberalism; Population